Standardization and Antioxidant Evaluation of Varatika Bhasma - B K Sarkar; K G Vasanthakumar; P Madhavikutty; V C Deep (Current Research in Pharmaceutical Sciences, 2013)
Current scenario lead to change in life style which has resulted in the increased production of free radicals which raise the oxidative stress and also play an important role in the immune system dysfunction. Hence there is need of a safe and effective antioxidant. In this regard Varatika Bhasm was screened for the free radical scavenging activity. Various antioxidant assay methods were used for this purpose such as hydroxyl radicals, super oxide radical scavenging activity and nitric oxide radical inhibition. Ascorbic acid (AA) was used as the standard antioxidant for the free radical scavenging assays. The study was carried out for different concentrations of drug in suspension form. The result of antioxidant activities shows significant scavenging of hydroxyl and super oxide radical with the minimum IC50 values of 54.8±0.53 mcg/ml and 91.21±0.22 mcg/ml respectively. Result of study suggested that Varatika Bhasm have excellent antioxidant activity against the different in vitro antioxidant models.